Protective effect of melatonin on adriamycin-induced cardiotoxicity in rats - Ayça Bilginoğlu; Duygu Aydın; Şeyma Özsoy; Hatice Aygün (KARE Publishing, 2014)
Objectives: Adriamycin is one of the most widely used anticancer drugs. The major limiting factor of using this drug is the development of cardiotoxicity. However, melatonin (N-acetyl- 5-methoxytryptamine) is a ubiquitous molecule as a good antioxidant that may protect the heart. We investigated whether or not pretreatment with melatonin can attenuate adriamycininduced cardiotoxicity. Study design: All procedures and experiments were approved by the Animal Ethics Committee of Gazi Osman Paşa University (2012-HADYEK-022). Adult male Wistar-Albino rats were randomly divided into four groups, namely control (CON, n=7), melatonin (MEL, n=7), adriamycin (ADR, n=7), and adriamycin+melatonin (ADR+MEL, n=7) groups. Cardiotoxicity in rats was induced by adriamycin injection (cumulative dose: 18 mg/kg, intraperitoneal [i.p.]) at an interval of 24 hours (h) on the 5th, 6th and 7th days. Rats receiving melatonin treatment in the adriamycin group received melatonin (10 mg/kg/day, i.p.) for 7 days and were injected with adriamycin (18 mg/kg, i.p.) on 5th, 6th and 7th days. On the 8th day, gravimetric, electrocardiography (ECG) and biochemical parameters were assessed. Results: Adriamycin induction caused changes in the ECG pattern, including ST-segment elevation and decreased Ramplitude, increase in the serum levels of cardiac injury markers (creatine kinase [CK], CK-MB, aspartate transaminase, and lactate dehydrogenase), decrease in the antioxidant enzymes activity (superoxide dismutase, glutathione peroxidase), elevated lipid peroxidation (malondialdehyde), and altered lipid profile in the serum. Melatonin treatment prevented all the parameters of adriamycin-induced cardiotoxicity in rats. Conclusion: Melatonin has a protective effect on the heart against adriamycin-induced cardiotoxicity in rats.